The Idea of Khalq al-Insān as the Goal of Human Life and Its Relevance to Islamic Education - Amaly, Abdul Mun’im; Ahmad EQ, Nurwadjah; Suhartini, Andewi (Research and Development Institution, Darussalam Institute for Islamic Studies, 2022)
The purpose of this research is to describe how Islamic education should achieve its goals in accordance with the concept of human creation as the subject and object of education. This study was conducted by a researcher using a literature review method, which involved reviewing a number of journal articles, books, research reports, and other credible literature. The study's findings indicate that the manifestation of the purpose of human life is essentially twofold: to be a servant of God, which is the actualization of God's mandate, and to become khalifāh in the world. Islamic education actualizes the two manifestations of the purpose of human life so that humans can realize their spiritual and bodily potential, and thus Islamic education plays an important role in the formation of a perfect human being in accordance with the concept of creation (khalq al-insān).